Multi-scale simulation and finite-element-assisted computation of elastic properties of braided textile reinforced composites - Ji, Xianbai (2014)
This article deals with the computation of effective elastic properties of braided textile composites assisted by finite element analysis. In this approach, dynamic representative unit cells are first constructed to model typical geometry of braided textile preform. After establishing the elastic properties of braiding yarns, the effective Young’s moduli, shear moduli and Poisson’s ratios corresponding to varying braiding angles are obtained by analysing these geometric models of preform with the help of the commercial finite element analysis code Abaqus. Effects of fibre volume fraction on the elastic properties of both biaxial and triaxial composite unit cells are also examined. Finally, the bending behaviour of a simply supported beam with braided composite skin is evaluated via the finite element analysis assisted multi-scale modelling, which is further verified experimentally. The predicted results were compared favourably with the experiment, backing the accuracy of the proposed modelling approach.